Effortful Control Predicts Adolescent Antisocial‐Aggressive Behaviors and Depressive Symptoms: Co‐Occurrence and Moderation by Impulsivity. Issue 6 (19th August 2015) - Wang, Frances L.; Chassin, Laurie; Eisenberg, Nancy; Spinrad, Tracy L.
Abstract : Effortful control is associated with fewer aggressive‐antisocial behaviors (AAB) and depressive symptoms (DEP), but impulsivity may moderate these relations. However, few researchers have considered the effects of AAB‐DEP co‐occurrence. A multi‐informant, multimethod approach assessed 5‐ to 10‐year‐olds' effortful control and impulsivity and, 5–6 years later, their AAB and DEP ( N = 474). Participants were non‐Hispanic Caucasian (59.2%) or Hispanic (27.9%) from a Southwestern U.S. metropolitan area. Low effortful control predicted pure AAB. Low effortful control and low impulsivity predicted pure DEP and co‐occurring AAB‐DEP. An effortful Control × Impulsivity × Age interaction predicted pure AAB and co‐occurring AAB‐DEP. For older adolescents, lower effortful control predicted more symptoms only at average and high impulsivity. Results highlight multiple pathways to pure DEP versus pure AAB or co‐occurring AAB‐DEP.